Accelerating land use carbon emissions in shrinking counties: a systematic analysis of land use dynamics in the Beijing-Tianjin-Hebei region, 2000–2020 - Zhang, Jianwen; Wang, Li; Fu, Meichen; Wen, Hongyan; Li, Sijia (Frontiers in Environmental Science, 2025)
Urban shrinkage, characterized by population loss and economic decline, poses unique challenges to carbon neutrality goals. While existing studies focus on energy-related emissions in shrinking cities, the role of land use dynamics remains underexplored. This study systematically investigates land use carbon emissions (LUCE) in shrinking counties to address this gap. Focusing on the Beijing-Tianjin-Hebei (BTH) region (2000–2020), we integrated population indices, land use data, energy statistics, and nightlight imagery to classify counties into non-shrinking, continuous, temporary, and potential shrinkage types. Direct and indirect carbon emissions were estimated using emission coefficients and energy consumption models. Key findings include: (1) Non-shrinking counties, concentrated in urban cores, exhibit higher LUCE but slower growth rates, whereas shrinking peripheral counties show lower emissions but faster LUCE growth. (2) Continuous shrinkage counties experience the highest LUCE growth due to inefficient built-up area expansion, despite having significant carbon sinks. (3) Severe shrinkage counties demonstrate the fastest total carbon emissions (TCE) growth, with per capita emissions (PCE) positively correlated to shrinkage intensity. These findings highlight the need for differentiated policies: prioritizing land-use efficiency in shrinking counties, integrating regional equity into emission governance, and leveraging carbon sinks in ecologically rich areas.